Implementation of the Sabaq Sabqi Manzil Method in Improving the Quality of Memory of the Qur'an: Case Study on Junior High School Students at the Imam Syafi'i Islamic Boarding School Tulungagung - M. Asep Fathur Rozi; Ali Mufron; Sofi’a Laila Tufa (DIMAR: Jurnal Pendidikan Islam, 2022)
Reading and studying the Quran is an obligation that must be done by Muslims. Reading and memorizing it is a worship that is worth a great reward. The Qur'an is the first source of law in Islam, the way of life for Muslims. This study takes the formulation of the problem regarding the application of the sabaq sabqi manzil method and the problems in improving the quality of memorizing the Qur'an at the Imam Syafi'i Islamic boarding school, Tulungagung. The researcher uses a qualitative research type, by taking data sources from the boarding school caregivers as resource persons and also documentation owned by the Islamic boarding school. Data were taken using in-depth interviews, observation and documentation studies. Researchers found that the method of memorizing the Qur'an greatly affects the quality of memorizing students if it is done regularly. This is proven by the number of students who read and memorize the Qur'an properly and correctly. The quality of the students' memorization has increased, as evidenced by when the students deposit their sabaq sabqi manzil they can do it well and smoothly. Because in essence the students are not just memorizing, but with this method the students will be required to repeat the memorization so that it becomes more imprinted and stronger.